Apatinib treatment for unresectable gastrointestinal stromal tumor with synchronous gastric cancer. Issue 1 (18th February 2020) - Xu, Huanji; Zhou, Sheng; Hu, Qiancheng; Cao, Dan
Abstract: Nearly one-fifth of patients diagnosed with gastrointestinal stromal tumors (GISTs) simultaneously experience a second primary tumor. In particular, coexistence of gastric GISTs and gastric cancer is relatively more common. However, the optimal treatment for advanced GIST with gastric cancer is largely unknown. We report a case of simultaneous occurrence of gastric GIST and gastric cancer that benefited from apatinib. After first-line imatinib and S-1 treatment for 6 months, the GIST and the gastric cancer both progressed. The patient was then treated with apatinib, exhibiting a partial response (PR) both in the GIST and the gastric cancer at 7 months, and continuous PR so far with well-controlled toxic effects of hypertension. Progression-free survival reached 10 months. In view of the relatively high incidence of advanced GIST with synchronous gastric cancer, therapy to simultaneously treat the two kinds of tumors is urgently needed. Apatinib provides promising and well-tolerated therapy for GISTs with synchronous gastric cancer refractory to chemotherapy combined with imatinib.